Ru(ii)-catalysed oxidative (4+2) annulation of chromene and coumarin carboxylic acids with alkynes/propargylic alcohols: isolation of Ru(0) complexes - Shankar, Mallepalli; Swamy, K. C. Kumara (Organic & biomolecular chemistry, 2022)
Ru(ii)-catalysed oxidative (4 + 2) annulation of chromene and coumarin-3-carboxylic acids with alkynes/propargylic alcohols via sp(2) C-H bond activation is reported. While the reaction with alkynes affords highly substituted pyrano-chromones in good to excellent yields, the use of methyl-tethered propargylic alcohols in place of alkynes leads to novel Ru(0)-metal complexes in moderate to good yields; these complexes were stable in MeCO2H/O-2. The generality of the reaction with alkynes is illustrated in the case of both symmetrical and unsymmetrical internal alkynes with excellent regioselectivity in the case of unsymmetrical alkynes.